Comprehensive character of the introduction and discussion of results from scientific reading in high impact factor journals - Argota-Pérez, George (2023)
The aim of the study was to describe the comprehensiveness of the introduction and discussion of results from the scientific literature in journals with a high impact factor. The study was conducted from January to June 2023. From the ScienceDirect database the search equation in English with the Boolean AND was: comprehension AND scientific information AND formative competence AND university students. The years 2021, 2022 and 2023 were filtered and 10 research articles were selected by non-probabilistic convenience sampling. The comprehensiveness towards the facilitation of alternatives and the discovery of obstacles was higher in the discussion of results. However, problem identification was recognized to be higher in the introduction: 80% > 20%. It was concluded that the comprehensiveness of scientific reading in high impact factor journals was described from three dimensions: identification of problems, facilitation of alternatives and discovery of obstacles. In each dimension, the percentage varied according to the methodological structure of the introduction and the discussion of results, being 80%, 36% and 44% for the former, and 20%, 64% and 56% for the latter.